Chronic Asymptomatic Pancreatic Hyperenzymemia: Is It a Benign Anomaly or a Disease? - Mariani, Alberto (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: ’San Raffaele’ biomedical/scientific park. Milan. Italy.